Budaya Organisasi Berbasis Nilai Agama Hindu - I Wayan Sukabawa (Kamaya: Jurnal Ilmu Agama, 2020)
This study aims to find the implementation of organizational culture, in this case the Ministry of Religion of the Regency of Buleleng based on Hindu values. The research method used was qualitative with the location of the Office of the Ministry of Religion in Buleleng Regency. Data collection techniques used were observation, interviews and document studies. Data analysis techniques include (1) data collection, (2) data reduction, (3) data presentation, and (4) conclusion drawing or verification. The implementation of organizational culture in the Office of the Ministry of Religion of Buleleng Regency especially in the Head of the Hindu Religion Affairs is inseparable from the role of the socialization of socio-cultural values themselves, both government leaders, traditional leaders, or family leaders. Theoretically, the process of institutionalizing values to society goes through several stages, including the stages known, understood, obeyed, and valued.